Daily Activities and Preferences of Macaca fascicularis towards Food Types as The Basis Conservation and Supporting Ecotourism in The Pengsong Mountain - M. Yamin; Dadi Setiadi; Khairuddin Khairuddin; Karnan Karnan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The Pengsong tourism area is a mountainous ecotourism area with beautiful natural scenery and attractive biodiversity, including the existence of the Macaca fascicular population. The type of Macaca fascicularis food is not yet known in the tourist area of Mount Pengsong, including carrying capacity of the population. The objectives of study are to determine the types of plants eaten and the types of food provided by visitors as well as the nutritional content of the food consumed by monkeys in the area, and the behaviours of Macaca fascicular as a management basis to support ecotourism in Mount Pengsong. The data collection was conducted using the “broad survey and line transect” method in the morning, afternoon and evening. The food data collected were include sources of food, drink, weathers, temperatures, moistures, slopes, altitude above sea level, and human activities in the vicinity. The behavioral data of Macaca fascicular studied were daily activities, mealtime, playing, resting, breeding, population structure, population disruptors, social patterns (solitary/pairs/groups) and cruising areas. As a result, the monkey diet in the form of plants was available around the tourist area as many as 23 species, 5 types of animals, 10 types of plant production in agricultural areas, and nine types of food provided by visitors. Nutritional needs and elements can be fulfilled from the availability of food sources and will be even more perfect by getting other food sources provided by visitors. Population control is needed so that the number of populations is in accordance with the carrying capacity of food sources. Macaca fascicular consumes a lot of plant species and is highly dependent on the availability of food in its environment, the food provided by visitors is favored by monkeys and provides good nutritional value. The Macaca fascicular population needs to be controlled so that it is in accordance with the carrying capacity of its environment and avoid damaging horticultural crops and plantation plants around the tourist area.